Study on the microscale structure and barrier mechanism of magnesium phosphate cement modified with fly ash cutoff walls for lead pollution in groundwater. (15th November 2021) - Ji, Xing; Ye, Changwen; Zhou, Jinqiu; He, Kui; Zhu, Rui; Xiang, Hang; Liu, Jiancheng; Xie, Zhenbin; Liao, Bing
Graphical abstract: Highlights: Magnesium phosphate cement modified with fly ash was synthesized as a kind of novel cutoff wall material. Permeability of the optimal sample can meet the anti-seepage and mechanical requirement. Internal structural parameters were analyzed through the pore-scale modeling. Permeability and velocity filed were simulated using the Lattice Boltzmann Method. The control effect of cutoff wall on Pb in groundwater was simulated by Visual MODFLOW. Abstract: Magnesium phosphate cement-fly ash (MPC-FA) has been synthesized as a new cutoff wall material to control lead pollution in groundwater. A series of experiments were conducted to investigate its properties including adsorption, mechanical performances, morphologies, microstructure and migration of Pb(Ⅱ) through the magnesium phosphate cement-fly ash cutoff walls. X-ray microcomputed tomography was used to get the microscale three-dimensional real geometry images of the cutoff walls. The internal structural parameters were analyzed through digital image processing technology. Lattice Boltzmann method (LBM) was employed to simulate the hydraulic conductivity and three-dimensional velocity fields distribution of cutoff walls. The optimized fly ash ratio (in mass) of cutoff walls was 40%, and the sodium dihydrogen phosphate/monopotassium phosphate molar ratio was 1:1. The compressive strength and flexural strength during 14 days were 23.2 MPa a nd 5.6 MPa, respectively. The laboratorial hydraulic conductivity of MPC-FA was 1.22 × 10 −9 m/s and the theoretical maximum adsorption capacity was 467.87 mg/g. The pore-network model showed that the connected porosity of MPC-FA was 14.45%, and the most of the pores and throats in cutoff walls were microflow paths (radius ≤ 12 μm). The hydraulic conductivity simulated by LBM basically coincided with the measured results, and the velocity fields indicated that the flow paths were tortuous and complex. Under different breakthrough concentration standards, the penetration of Pb(Ⅱ) at initial concentration of 4000 mg/L through cutoff walls with thickness of 0.6 m, 1 m, 1.2 m, 1.5 m needed 8–10, 22–28, 31–41 and 49–64 years, respectively. The model obtained by Visual MODFLOW numerical simulation showed that the contaminant plume of Pb(Ⅱ) was controlled after 7400 days in the polluted site with MPC-FA cutoff walls, which supported that the MPC-FA met the requirements for good control of Pb(Ⅱ) in the lead-contaminated sites.